2016
DOI: 10.1108/et-04-2016-0064
|View full text |Cite
|
Sign up to set email alerts
|

Threshold concepts in business school curriculum – a pedagogy for public trust

Abstract: Purpose -The purpose of this paper is to explore some of the implications for curriculum design by operationalizing threshold concepts and capabilities (TCC) in subject delivery. The motivation for undertaking this exploration is directly related to addressing public concerns for the business school curriculum. Design/methodology/approach -A post facto analysis of a compulsory subject in finance that is part of an Australian business degree and the impact on a subsequent finance subject. Findings -Customary ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…Although it is important to include the thresholds in the curriculum, these should also be properly addressed in teaching and assessment (Bajada et al, 2016), in line with the principles of constructive alignment presented by Biggs (2003). The constructivist teaching activities pointed out in this research will be helpful for teachers when developing their teaching to support overcoming the thresholds.…”
Section: The Choice Of Educational Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although it is important to include the thresholds in the curriculum, these should also be properly addressed in teaching and assessment (Bajada et al, 2016), in line with the principles of constructive alignment presented by Biggs (2003). The constructivist teaching activities pointed out in this research will be helpful for teachers when developing their teaching to support overcoming the thresholds.…”
Section: The Choice Of Educational Methodsmentioning
confidence: 99%
“…This teacher concluded that of course full score could be given provided that the prioritization is well performed. This connects to Bajada et al (2016) stating that if the intended learning aspects (in this example critical evaluation and contextual adaptation) are not assessed, the students might misunderstand what is essential to learn. However, it is crucial that the students know and trust the teacher's intentions; otherwise, they might still think that they should include everything.…”
Section: Alignment Between Teaching and Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In economics, the concept of opportunity cost has been identified as a concept that is difficult to learn (O'Donnell, 2015). In business, certain aspects of business finance have been identified as threshold concepts (Bajada, Jarvis, Trayler, & Bui, 2016). Photosynthesis and enthalpy have been researched in this context of threshold concepts in biology (Kinchin, 2010) and chemistry (Chandler-Grevatt, 2015), respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Management educators have reported the positive impact of threshold concepts on learning outcomes (Bolinger & Brown, 2015; Burch, Burch, Bradley, & Heller, 2015; Crispin et al, 2016; Donovan, 2017; Hawkins & Edwards, 2013; Hibbert & Cunliffe, 2015; Nahavandi, 2016; Nichols & Wright, 2015; Wright & Hibbert, 2015; Wright & Gilmore, 2012; Vidal, Smith, & Spetic, 2015; Yip & Raelin, 2012). Furthermore, the focus on the development of threshold capabilities is emerging (Bajada, Jarvis, Trayler, & Bui, 2016; Crispin et al, 2016). Threshold capabilities refer to learning beyond content and focus on developing skills for future practice (Baillie, Bowden, & Meyer, 2013).…”
mentioning
confidence: 99%